Digital Ecosystem Development Strategy at PT Bank Sulselbar - Aiman Nuraddin; Mashur Razak; Didi Haryono (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to formulate a digital ecosystem development strategy at PT Bank Sulselbar by identifying the institution’s internal strengths and weaknesses and the external opportunities and threats affecting digital banking transformation. The research applies a descriptive qualitative design using interviews, observation, documentation, and triangulation. Data were analyzed inductively through data reduction, data display, conclusion drawing, and verification, and were subsequently synthesized using IFAS, EFAS, and SWOT analysis. The findings show that Bank Sulselbar has strong technological infrastructure, customer trust, partnership networks, capital support, and regulator-backed digital services. Internal constraints include uneven access to digital devices and internet connectivity, gaps in employee digital competence, increasing system complexity, and dependence on third parties. Externally, the growth of internet use, rising demand for fast and secure banking services, technological innovation, and opportunities for collaboration support ecosystem expansion. Conversely, fintech competition, cyberattacks, shortages of digital talent, changing regulations, and poor user experience remain significant threats. The internal index of 0.21 and external index of 0.34 place the bank in Quadrant I, indicating an aggressive growth strategy. Accordingly, Bank Sulselbar should accelerate service innovation, strengthen cybersecurity, improve application usability, develop employee capabilities, expand partnerships with fintech and technology firms, and use artificial intelligence and big data to support inclusive financing. These measures can enhance operational efficiency, accessibility, customer convenience, and competitiveness while maintaining consumer trust and supporting regional economic development.